CONCUSSION KNOWLEDGE, ATTITUDES, AND BELIEFS AMONGST SPORTS MEDICINE PERSONNEL AT THE 2015 CEREBRAL PALSY FOOTBALL WORLD CHAMPIONSHIPS. Issue 4 (1st February 2017) - Griffin, Steffan; West, Liam Richard; Ahmed, Osman Hassan; Weiler, Richard
Abstract : Background: Concussion poses a challenge to sports medicine personnel, especially those working in contact sports such as football. In disability sport, the correct assessment and management of this injury is paramount. Objective: To determine knowledge, attitudes, and beliefs regarding concussion amongst team physicians/physiotherapists working at the 2015 Cerebral Palsy Football World Championships (CPFWC). Design: A 22-item questionnaire was provided to the 'head of medicine' of all teams participating at the 2015 CPFWC (n=15). Qualitative assessment of knowledge, attitudes and beliefs of participants in regard to concussion; both generally, and specifically to cerebral palsy football. Setting: 2015 CPFWC, St George's Park, Burton-upon-Trent, United Kingdom. Patients (or Participants): Each nation's head of medical services (n=15; either a medical doctor or physiotherapist) were invited to complete the questionnaire during the pre-competition medical meeting. Interventions (or Assessment of Risk Factors): NA. Main Outcome Measurements: Knowledge, attitudes, and beliefs related to concussion amongst sports medicine professionals at a World Championship. Results: The majority of participants (8 physiotherapists and 6 doctors: or 93%) completed the questionnaire. Only one practitioner did not score 100% on identifying the signs and symptoms of concussion. 36% (n=5) believed headgear had protective effects against concussion. The use of a concussion assessment tool following suspected concussion was reported by 29% (n=4) clinicians, whilst 50% (n=7) stated that performing cognitive assessments were difficult in this population. 86% participants (n=12) reported that a disability sport concussion consensus statement would be useful. Conclusions: Participants' overall knowledge around concussion was sound, but their methods for recognition and management were highly variable. Inherent difficulties were identified in the assessment and management of concussion in disabled athletes and the majority recognised an urgent need for expert clinical guidance for this population.